Energy Harvesting with a Piezoelectric Thunder - Wang, Fengxia; Wu, Wei; Soroush, Mahmoudiandehkordi; Abedini, Amin (Journal of Applied Nonlinear Dynamics, 2026)
In this work the energy harvesting performance of a piezoelectric curved energy generator (THUNDER) is studied via experimental and analytical methods. The analytical model of the THUNDER is created based on the linear mechanical electrical constitutive law of the piezoelectric material, the linear elastic constitutive law of the substrate, and the Euler-Bernoulli beam theory. With these linear modal functions, the Rayleigh-Ritz approach was used to then obtain the reduced mechanical electrical coupled modulation equations. With above analytical model, two types of energy harvest circuit are proposed and compared: 1) directly charging mode at low level excitation, and 2) memory stored optimal duty cycle step-down converter mode at high level excitation. The value of the optimal duty cycle is determined based on the characteristics of the vibration signals of the ambient vibration source. To reduce the energy consumption of the microcontroller, the optimum duty cycle values are stored in the microprocessor instead of doing onsite computing during energy harvesting process. For the purpose of designing a low power cost mechanical switch to control the operation of both modes, the threshold voltage between these two operation modes is converted into threshold displacement.